Caracterização populacional e plasticidade morfológica de duas populações hololimnéticas de Macrobrachium amazonicum (Decapoda, Palaemonidae) - Cunha, Marina Calixto (2019)
The present study sought to understand variations in demographic, morphological and sexual ratio characteristics of two populations of the caridean shrimp Macrobrachium amazonicum, located in the Triângulo Mineiro region in the Araguari (Miranda Hidroeletric Power Plant – lentic environment) and Rio Grande (downstream of Igarapava HPP - lotic environment) river basins and how these populations fit into the following clades proposed by Vergamini et al. (2011): 1- Amazon Basin continental region; 2 - Paraná / Paraguay Basin continental region; 3 - North and Northeast coastal regions of the. Two samples were carried out at each river. For shrimp sampling, covo traps (27h sample / point) and sieves (1h sample / point) were used. Specimens were identified, sexed, had carapace length (CC) measured with an analog caliper for posterior frequency distribution in classes of 1 mm CL and classified in young and adult. Males were divided into morphotypes according to cheliped staining and size differentiation between carpus and propodus. Morphological data and frequency of individuals by demographic categories of the populations were compared using Student's t-test and the sex ratio using Chi-square and Binomial Test. Based on a bibliographical survey, data on sex ratio and CLmax of populations from different regions in Brazil were compiled to compose a meta-analysis. The criterion for the selection of papers was to have complete data referring to sex ratio, CLmax and sampling location. At least one region of each clade proposed above was sampled. The data were evaluated through a principal component analysis (PCA). A total of 703 individuals were sampled in the Araguari River (366 females, 337 males), organized in eight classes of CL (4 - 11 mm), with sexual ratio 1Macho: 1.1 Females and females larger than males. In Grande River, 808 individuals were sampled (575 females, 233 males), distributed in 21 CL classes (4 - 24 mm). The males were divided in three morphotypes: Transparent Claw, Cinnamon Claw and Green Claw, but the average CL size of females and males did not differ. The sex ratio was 1Male: 2.5 Females. In the meta-analysis, 22 populations were considered, which were distributed between lentic and lotic environments, brackish and freshwaters and could be characterized as hololimnetic and amphidrome. Through the PCA, it was verified that the populations of the Araguari River seem to be framed in clade 2 (Paraná Basin / Paraguay) and the populations of Grande River are divided between clades 1 (Continental Amazon Basin) and 2. The data obtained indicate that both populations adopt different reproductive strategies and these strategies can interfere in the differences of demographic categories found, as well as in the presence or absence of morphotypes of males. It is also possible to infer that Grande River may have been configured as an area that maintained gene flow between populations of clades 1 and 2 and it is a fundamental area in maintaining the genetic variability of this species.